Increase life of Cluster Head in Wireless Sensor Network by using LEACH Protocol (International Journal of Advanced Research in Computer Science, 2017)
In case of detector network the nodes loss some quantity of energy once performing the communication. To boost the lifetime of network a energy economical communication approach is needed. In case of multicast network an collective approach is employed by LEACH protocol by creation of chain of nodes. The given work is the improvement over the LEACH protocol individual to some parameter. Here we are proposing the three call parameters to pick following node in network .These parameters embrace the space, energy and also the residual energy. The projected work can improve the potency even in case of engorged and congested network and improve the network life. Sensing element network is the large set of small sensors that transfer small piece of data. As it forms a huge range of sensors it suffers from the matter of QOS. Every sensing element node consumes some energy with totally different communication operations. If no external energy is provided to them, a sensing element can be dead because it participates for long-standing within the communication. The planned work is proposed to improve the network life- time in case of LEACH protocol. It's a Cluster based protocol and transfer information to at least one of its neighbor node supported distance. During this planned work we are going to take the choice primarily based on the remaining energy on transmission. If the remaining energy is a smaller amount than the threshold, it'll communicate to some compromising node rather than effective distance node. The work is about to provide higher utilization of energy and to enhance the node and network life.Keywords: Wireless Sensor Network; leach protocol; Node; BS Base Station; Wi-Fi